Enhanced Falling Film Heat Transfer - Sanches Romeiro, Rita (My University, 2009)
The increase in the global energy demand along with the increased concern about the carbon emission requires a general reduction of the energy consumption. The industry sector, which is one of the main energy consumers, has been investigated for a long time and performed studies have identified great potentials in reducing the energy consumption and increasing their efficiency. This work aim to provide more information in this area, as it intends to present a basis for the development of the enhancement technology for falling film evaporation. This enhancement was accomplished by the use of extended surfaces which have proved to increase the efficiency of the heat and mass transfer process. Experiments were conducted on a falling film evaporator/heater, built in cooperation with Metso Power AB, Göteborg and Chalmers University of Technology. A five meters tube was used, of which one meter was internally heated and made of copper, so its enhancement with copper wires of different diameters was possible. After the calibration process, experiments were conducted using water as the working fluid and several enhancement configurations. The analysis of the results revealed that not all the diameters could be tested due to flow separation. On the other hand if small diameters were tested, the result shows that the additional area could not promote as much turbulence and then would be unable to remove enough heat. Subsequent tests were conducted with the intent of investigating the viscosity effect, in which the working fluid was replaced by an aqueous solution of propylene-glycol, which had a viscosity ten times higher than water. The results showed the obtained enhancement was higher than the ones registered for water. It is also interesting to notice the optimum pitch distance for one defined volume flow can be bigger when the viscosity increases, due to the reduced turbulence of high viscosity fluids and consequently, smaller recirculation areas after the wires. Nevertheless, there is a defined and similar trend in the all the curves, despite the different viscosities. It is recommended the best configuration chosen should be insensitive to volume flow changes.
Keywords: Kemisk energiteknik; Chemical energy engineering